JOKE TRANSLATION AND CULTURE - Soatova Mohinur Majid qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. Humor is a universal phenomenon that exists in all cultures, yet it is profoundly shaped by cultural norms, values, and experiences. Translating jokes from one language to another is a complex task because humor often relies on cultural references, linguistic nuances, and shared context. A successful joke translation must not only convey the original meaning but also evoke the same humorous effect in the target culture. This essay explores the challenges and strategies of translating jokes and highlights the role of culture in shaping humor.